Social Support and the Implementation of the Early Initiation of Breastfeeding (IMD) among the Madurese in Indonesia - Yunitasari, Esti; Pitaloka, Pipit; Mariyanti, Herdina; KeeJiar, Yeo (International Journal of Psychosocial Rehabilitation, 2020)
This study is focused on the early initiation of breastfeeding referring to infants receiving breastfeeding within the first hour after birth. The early initiation of breastfeeding can reduce infant mortality and it is crucial for newborn survival. However, the implementation of the Early Initiation of Breastfeeding (IMD) initiative seems to fail in some areas. The purpose of this study was to determine the relationship between social support and the implementation of IMD among the Madurese of Indonesia. This study employed a cross-sectional design. The sample consisted of 76 postpartum mothers at the Sreseh Health Center, Sampang Regency. A questionnaire was used as the instrument for the data collection. Spearman rank correlation was used to determine the relationship at a significance level of p < .05. The results of the statistical test (r=0,703 n= 76 p=.00) showed that social support was related to IMD implementation. Most of the respondents did not implement IMD and the level of social support was low. The lowest support offered was information support and the highest level of social support was obtained from the religious or community leaders. This analysis leads to the conclusion that the increased IMD implementation needs social support from the people around the mothers such as the health workers. These people can provide counseling and information about the importance of the Early Initiation of Breastfeeding (IMD).